MEANING IN THE FAMILIAR AND IN THE STRANGE WORLD (Andamios, Revista de Investigación Social, 2008)
The present article is based in the phenomenology of Edmund Husserl and Alfred Schütz. We attempt to show parallels between both thinkers as regards the assimilation of one’s own culture and foreign cultures, and we also consider a similarity between the need to remake education and internalize foreign cultural patterns when attempting to gain access to a foreign community. We notice the determinant characteristic of language in its communicative function and we stress the importance of the notion of ideal types, not only in the attitude of natural thought but also in the interest of social science specialists. Philosophical thought remains implicit with regard to the foundation of the social sciences.
Keywords: Language; communication; types; education; cultures